2018
DOI: 10.1016/j.oraloncology.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

UM-HACC-2A: MYB-NFIB fusion-positive human adenoid cystic carcinoma cell line

Abstract: Objectives: Limited availability of validated human adenoid cystic carcinoma (ACC) cell lines has hindered the mechanistic understanding of the pathobiology of this malignancy and the development of effective therapies. The purpose of this work was to generate and characterize a human ACC cell line. Material and Methods: Immediately after surgery, a tumor fragment from a minor salivary gland from the tongue of a female Caucasian was minced, dissociated, and a single cell suspension was plated in fibronectin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…We additionally predicted the targets of miR-346 using miRWalk2.0 and TargetScan. NFIB, a previously reported tumor promotor in many kinds of cancers [24], shared sequence complementarity in its 3′-UTR with the miR-346 seed sequence, which was confirmed by luciferase report assays. PCR and western blot results showed that overexpression of miR-346 downregulated the expression of NFIB, indicating a negative correlation.…”
Section: Discussionsupporting
confidence: 67%
“…We additionally predicted the targets of miR-346 using miRWalk2.0 and TargetScan. NFIB, a previously reported tumor promotor in many kinds of cancers [24], shared sequence complementarity in its 3′-UTR with the miR-346 seed sequence, which was confirmed by luciferase report assays. PCR and western blot results showed that overexpression of miR-346 downregulated the expression of NFIB, indicating a negative correlation.…”
Section: Discussionsupporting
confidence: 67%
“…Finally, Warner et al reported one ACC cell line with retaining MYB‐NFIB fusion genes by adding cytokines, rhEGF, human hydrocortisone and human insulin to conventional medium in 2D culture. To date, only Warner et al successfully established an orthotopic xenograft using their cell line; however, its tumor was only micro‐HLA‐positive cell clusters in the submandibular gland lymph nodes without recapitulating the histological characteristics of original ACC tumor 10 . Overall, it seems that it is difficult for ACC cell lines established in 2D culture to reproduce at least the histological architecture of human salivary ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary ACC is now characterized by frequent representation of MYB‐NFIB/MYBL1‐NFIB fusion gene 5 as well as high MYB expression 6‐9 . The role of these gene fusions on carcinogenesis of ACC has started to be examined widely; however, our understanding of the ACC biology is still incomplete mainly due to limited availability of reliable ACC cell line 10 . The paucity of in vitro and in vivo salivary ACC models is thus hampering the progress of new drug development for patients with these malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mitani et al reported that the level of MYB expression in identical histological subtypes of ACC is associated with a shorter survival time. Recently, xenografting and the first MYB‐NFIB‐positive cell line (UM‐HACC‐2A) have been established and represent interesting tools to explore novel therapeutic possibilities . Therapeutically, MYB‐targeted antisense oligodeoxynucleotides (G4460; INX‐3001; LR3001) have not been effective in clinical trials ; however, several lines of evidence suggest that MYB is a promising therapeutic target .…”
Section: Discussionmentioning
confidence: 99%